Inhibition or Stimulation of Ochratoxin A Synthesis on Inoculated Barley Triggered by Diffuse Coplanar Surface Barrier Discharge Plasma - Durek, Julia; Schlüter, Oliver; Roscher, Anne; Durek, Pawel; Fröhling, Antje (Frontiers in Microbiology, 2018)
Ochratoxin A (OTA) is one of the most abundant food-contaminating mycotoxins. Besides their high toxicity, mycotoxins are highly stable to physical, chemical or biological detoxification. Therefore, the treatment with cold atmospheric plasma could be one approach to reduce the amount of mycotoxins in different products. The aim of this study was to determine the influence of cold atmospheric plasma on the inactivation of Aspergillus niger and Penicillium verrucosum inoculated on barley and their production of OTA. Inoculated barley was treated with plasma generated by dry air, CO2 or CO2 + O2 for 1 or 3 min and stored for up to two weeks at 9, 25 or 37 °C. Three minutes of air plasma treatment effectively significantly reduced the total mold count of both microorganisms by 2.5-3 log cycles. The production of OTA from A. niger was only low, therefore the treatment effect was indistinguishable. The treatment of P. verrucosum on barley after an incubation of five days using a CO2 + O2 plasma resulted in a reduction of the OTA content from 49.0 (untreated) to 27.5 (1 min) and 23.8 ng/g (3 min), respectively. In contrast, CO2 plasma caused an increase of the OTA amount from 49.0 (untreated) to 55.8 (1 min) and 72.9 ng/g (3 min). Finally, the use of air plasma resulted likewise in a decrease of the OTA concentration from 56.9 (untreated) to 25.7 (1 min) and 20.2 ng/g (3 min), respectively. Reducing the incubation time before the treatment to 24 h caused in contrast an increase of the OTA content from 3.1 (untreated) to 29.1 (1 min) and 20.7 ng/g (3 min). Due to the high standard deviation, these changes were not significant, but the tendencies were clearly visible, showing the strong impact of the plasma gas on the OTA production. The results show, that even if the total mold count was reduced, under certain conditions the OTA amount was yet enhanced, probably due to a stress reaction of the mold. Concluding, the plasma gas and incubation conditions have to be considered to allow a successful inactivation of molds and in particular their toxic metabolites.